Rethinking civil society and transitional justice: lessons from social movements and 'new' civil society. Issue 7 (2nd September 2017) - Gready, Paul; Robins, Simon
ABSTRACT: Transitional justice has often reduced conceptions of civil society to human rights NGOs, and lacks a rigorous conceptualisation of the role that civil society plays in transitional justice processes. It largely ignores as political actors the social movements that have driven democratisation in various parts of the world and can be credited as integral to the creation of the discourse of transitional justice. While transitional justice in theory and practice remains focused on traditional civil society, institutions and the state, recent transitions highlight that change is driven by a range of different actors, often using modes of organisation and repertoires of action linked to social movement modalities and other forms of collective action. As such we coin the term 'new' civil society, associated with events such as the Arab Spring and austerity-led protests in Southern Europe, to argue that it provides new models for understanding change and justice in transition. An effort is made to conceptualise the roles civil society can play in shaping transitional justice and the 'new' civil society framework is used to understand how such actors actively contest mainstream social, political and transitional paradigms, and model alternatives to them. 'New' civil society actors rethink how justice and rights are understood in transition, and model alternatives that constitute new forms of transitional politics.